1995
DOI: 10.2337/diacare.18.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Gestational Diabetes and Adiposity on Neonatal Adiposity and Blood Pressure

Abstract: Increased maternal prepregnancy weight, weight gain in pregnancy, and glycemia in pregnancy all place IGDM at increased risk of macrosomia and adiposity. Increased adiposity in the IGDM appears to be related to increased infant blood pressure. Longitudinal evaluation is needed to determine whether neonatal adiposity in IGDM is predictive of increased adiposity and blood pressure during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 24 publications
2
28
1
Order By: Relevance
“…Other investigators have shown an association between single maternal glucose parameters and macrosomia at birth [15,22,34], but the glucose values of these study populations were higher than in our investigated cohort. Our study population consisted of women with mostly mild glucose intolerance due to our low diagnostic criteria and the inclusion of women with IGT and good glucose control was achieved during pregnancy.…”
Section: Commentscontrasting
confidence: 83%
“…Other investigators have shown an association between single maternal glucose parameters and macrosomia at birth [15,22,34], but the glucose values of these study populations were higher than in our investigated cohort. Our study population consisted of women with mostly mild glucose intolerance due to our low diagnostic criteria and the inclusion of women with IGT and good glucose control was achieved during pregnancy.…”
Section: Commentscontrasting
confidence: 83%
“…[5][6][7] GDM is well known for its disastrous impact on the fetus in terms of perinatal mortality and morbidity and also on the mother for obstetrical complications. [8][9][10][11][12][13][14][15][16] Hyperglycemia in the first trimester of pregnancy may lead to congenital malformations. Common malformations are anencephalus, hydrocephalus, spina bifida, caudal regression, ear and eye anomalies, ventricular septal defect, atrial septal defect, transposition of great vessels, and renal and rectal anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…With gestational diabetes, the fetus is exposed to high levels of both glucose and amino acids, and the resulting fetal hyperglycemia is associated with increased insulin secretion (hyperinsulinemia) and accelerated growth of lean body mass and fat. 6,36 Davies 37,38 followed 51 SGA and 38 LGA infants, defined as below or above the 5th and 95th percentiles, 39 respectively, compared with 100 AGA controls. During the first 6 months, there were substantial shifts to the mean in weight, but great diversity in growth pattern.…”
Section: Commentmentioning
confidence: 99%